Findings of the Association for Computational Linguistics: EMNLP 2021 2021
DOI: 10.18653/v1/2021.findings-emnlp.305
|View full text |Cite
|
Sign up to set email alerts
|

TAG: Gradient Attack on Transformer-based Language Models

Abstract: Although distributed learning has increasingly gained attention in terms of effectively utilizing local devices for data privacy enhancement, recent studies show that publicly shared gradients in the training process can reveal the private training data (gradient leakage) to a third party. However, so far there hasn't been any systematic study of the gradient leakage mechanism of the Transformer based language models. In this paper, as the first attempt, we formulate the gradient attack problem on the Transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…Despite substantial progress on image reconstruction, attacks in other domains remain challenging, as the techniques used for images rely extensively on domain specific knowledge. In the domain of text, in particular, where federated learning is often applied (Shejwalkar et al, 2021), only a handful of works exist (Zhu et al, 2019;Deng et al, 2021;Lu et al, 2021). DLG (Zhu et al, 2019) was first to attempt reconstruction from gradients coming from a transformer; TAG (Deng et al, 2021) extended DLG by adding an L 1 term to the reconstruction loss; finally, unlike TAG and DLG which are optimization-based techniques, APRIL (Lu et al, 2021) recently demonstrated an exact gradient leakage technique applicable to transformer networks.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite substantial progress on image reconstruction, attacks in other domains remain challenging, as the techniques used for images rely extensively on domain specific knowledge. In the domain of text, in particular, where federated learning is often applied (Shejwalkar et al, 2021), only a handful of works exist (Zhu et al, 2019;Deng et al, 2021;Lu et al, 2021). DLG (Zhu et al, 2019) was first to attempt reconstruction from gradients coming from a transformer; TAG (Deng et al, 2021) extended DLG by adding an L 1 term to the reconstruction loss; finally, unlike TAG and DLG which are optimization-based techniques, APRIL (Lu et al, 2021) recently demonstrated an exact gradient leakage technique applicable to transformer networks.…”
Section: Related Workmentioning
confidence: 99%
“…In the domain of text, in particular, where federated learning is often applied (Shejwalkar et al, 2021), only a handful of works exist (Zhu et al, 2019;Deng et al, 2021;Lu et al, 2021). DLG (Zhu et al, 2019) was first to attempt reconstruction from gradients coming from a transformer; TAG (Deng et al, 2021) extended DLG by adding an L 1 term to the reconstruction loss; finally, unlike TAG and DLG which are optimization-based techniques, APRIL (Lu et al, 2021) recently demonstrated an exact gradient leakage technique applicable to transformer networks. However, APRIL assumes batch size of 1 and learnable positional embeddings, which makes it easy to defend against.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations